OPTIMALISASI NILAI GUNA SAMPAH SEBAGAI PUPUK KOMPOS UNTUK BUDIDAYA SAYURAN SECARA VERTIKULTUR - Sumiasih, Inanpi Hidayati (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Hygiene is an important aspect in everyday life. However, in some areas there is still waste that is just thrown away and mixed between organic and inorganic waste. These wastes should still be utilized as products that are useful for everyday life or used to increase the value of waste by making products that are worth selling. For example in an organic waste can be used to make compost fertilizer (compost can come from leftovers such as leftover vegetables and fruits that cannot be eaten), while inorganic waste can be used for making verticulture (this product can be used as a place to grow vegetables or flowers). The socialization and training in making compost for vegetable cultivation vertically is one way to increase the interest and talent of the community in Cibitung Kulon village. The compost training is not only used to grow vegetables vertically in the yard of the house and in the cultivation of vegetables in the farmer's garden, but it is also intended to help farmers in the maintenance / cultivation of rice plants or food crops in order to reduce the use of chemical fertilizers. This verticulture training in composting and vegetable cultivation is conducted in August 2018 in the Cibitung Kulon Village Office Hall RW 7, Pamijahan District, Bogor. The results of the implementation of training activities in making compost and growing vegetables vertically in Cibinong Kulon, RW 07, Pamijahan District, Bogor went well. This can be seen from the enthusiasm of the many participants present and the involvement of the community in following a series of activities that have been well prepared from the beginning to the end of the activity.Keywords: Environment, Household Fertilizer, Hygiene, Organic, Plants